Sequence-dependent cross-resistance of combined radiotherapy plus BRAFV600E inhibition in melanoma. (March 2019) - Shannan, B.; Matschke, J.; Chauvistré, H.; Vogel, F.; Klein, D.; Meier, F.; Westphal, D.; Bruns, J.; Rauschenberg, R.; Utikal, J.; Forschner, A.; Berking, C.; et al.
Abstract: Introduction: Treatment of patients with metastatic melanoma is hampered by drug-resistance and often requires combination with radiotherapy as last-resort option. However, also after radiotherapy, clinical relapses are common. Methods & results: Our preclinical models indicated a higher rate of tumour relapse when melanoma cells were first treated with BRAF V600E inhibition (BRAFi) followed by radiotherapy as compared to the reverse sequence. Accordingly, retrospective follow-up data from 65 stage-IV melanoma patients with irradiated melanoma brain metastases confirmed a shortened duration of local response of mitogen-activated protein kinase (MAPK)-inhibitor–pretreated compared with MAPK-inhibitor–naïve intracranial metastases. On the molecular level, we identified JARID1B/KDM5B as a cellular marker for cross-resistance between BRAFi and radiotherapy. JARID1B high cells appeared more frequently under upfront BRAFi as compared with upfront radiation. JARID1B favours cell survival by transcriptional regulation of genes controlling cell cycle, DNA repair and cell death. Conclusion: The level of cross-resistance between combined MAPK inhibition and radiotherapy is dependent on the treatment sequence. JARID1B may represent a novel therapy-overarching resistance marker. Highlights: Higher rate of tumour relapse under upfront mitogen-activated protein kinase (MAPK)-inhibition as compared with upfront radiation. JARID1B/KDM5B high cells appeared more often under upfront MAPK-inhibition as compared with upfront radiation. JARID1B/KDM5B may represent a novel therapy-overarching (cross-) resistance marker.